Bosworthova zlomenina hlezna (kazuistika) - Jehlicka, D; Bartonícek, J; Rysavý, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2001)
The authors describe an atypical case of the so called Bosworth fracture of ankle. A woman, 26 years suffered a fracture of fibula in the proximal third of the shaft, the distal fibular fragment was displaced from the fibular insicure of distal tibia posteromedially where it remained locked behind posterior tibial tubercle, and a fracture of medial malleolus and fracture of the posterolateral fragment of distal tibia. Thus it was a fracture-dislocation of ankle of Weber C type. The primary examination showed an evident external rotation deformity of the foot with regard to tibia. Conservative reduction was performed with a subsequent surgical revision, fixation of medial malleolus, suture of anterior tibiofibular ligament and stabilization of the reduced fibula in the fibular insicure of distal tibia by a suprasyndesmal screw. At present, four years after the surgery the patient is fully satisfied. Objectively there occurred only a limitation of dorsiflexion in ankle by 10 degrees as compared to the contralateral joint. Radiograph shows healing of the fracture in the anatomical position, without sings of post-traumatic osteoarthritis. Analysis of literature has showed that only approximately 40 cases with various sub-types of this fracture have been so far described. Typical of all fractures is a marked external rotation of the foot with regard to tibia, radiograph shows posterior subluxation of talus with regard to distal tibia and posteromedial dislocation of distal fibula from the fibula insicure of distal tibia and its locking behind its posterior tubercle. Apart from the above mentioned, associated with the injury is always a rupture of anterior tibiofibular ligament and partial rupture or distension of posterior tibiofibular ligament. In a typical Bosworth fracture it is associated with fracture of lateral malleolus of Weber B fracture. Very frequent is also a minor avulsion of the posterolateral fragment of distal tibia. In atypical cases fibula breaks in its proximal third (this Weber C type of fracture is described only by Hamilton) or there is no fracture of fibula. In children or young adults fibula does not break, it only dislocates and in adolescents there may simultaneously occur epiphysiolysis of distal tibia. On the medial side there usually occurs a fracture of medial malleolus or rupture of deltoid ligament or there is no lesion on the medial side. Conservative reduction is successful only exceptionally, i.e. only in case of intact fibula or its high fracture (Weber C), the method of choice is open reduction and internal fixation.
Keywords: fibula; ženské pohlaví; poranění kotníku; dospělí; Humans; Adult; Fibula; Female; Fractures, Bone; Ankle Injuries; fraktury kostí; lidé